Efektivitas Penerimaan Sektor Pajak Restoran, Perhotelan, Dan Penerangan Jalan Untuk Meningkatkan Pendapatan Asli Daerah Kota Langsa - Zulfa Eliza; Zikriatul Ulya; Husnul Khatimah (Pusat Riset dan Inovasi Nasional, 2023)
Regional autonomy can indeed bring about positive changes in the regions in terms of regional authority to self-regulate. Tax is a source of state or regional revenue that is paid by the community as a collection fee that can be imposed by the government based on applicable regulations. The aims of the research are a) to find out how effective the revenue from the restaurant tax sector, hotel tax, and street lighting tax are Regional Own Revenue in Langsa City, b) to find out what factors are inhibiting the revenue from the restaurant, hotel, and street lighting tax sector as income. Original area and government efforts to overcome obstacles in the restaurant tax revenue sector, this study uses a qualitative approach. The effectiveness of tax revenue from the restaurant sector, hotel sector, and the tourism sector from 2016-2020 from the results of the data that the researchers obtained, there were still achievements in accordance with the targets set by the government, such as from the tourism sector, this was due to the constraints of the Covid-19 virus outbreak so that there is implementation on a large scale so that the tourism sector does not get a nominal amount as Regional Original Income. In its application, there are inhibiting factors, including the names of restaurants and hotels that have not been recorded by the Regional Original Revenue Service, so that the effectiveness in receiving both types of taxes is not fully maximized.